Biodegradation of Plastic and the Role of Microbial Enzymes in Plastic Waste Management - Abubakar Muhammad Hammari; Abubakar Aisami; Maryam Ibrahim; Muhammad Jauro Jauro; Usman Adamu Bashir (Darul Yasin Al Sys, 2026)
Plastic pollution has emerged as a major environmental problem affecting terrestrial and aquatic ecosystems and posing human health risks through microplastic exposure and chemical leaching. This research reviews the biodegradability of common plastics and examines biological approaches—particularly microbial and enzymatic degradation—as complementary strategies to mechanical and chemical recycling. Drawing on recent experimental and review literature, it describes microbial colonization of plastic surfaces and the enzymatic mechanisms underlying depolymerization, with emphasis on PET hydrolases such as PETase and MHETase, cutinases, and oxidative enzymes including laccases. The study further outlines analytical methods for assessing plastic degradation and evaluates strategies to enhance enzymatic depolymerization, such as protein engineering, enzyme immobilization, and physical or chemical pretreatment of substrates. In addition, it discusses scale-up challenges, biosafety considerations, and pathways for integrating biotechnological solutions into circular economy frameworks, and formulates recommendations for future research and pilot-scale deployment. Overall, the review highlights the potential and limitations of microbial and enzymatic plastic biodegradation as part of a broader portfolio of interventions needed to mitigate plastic pollution.